Environmental justice and the new pluralism : the challenge of difference for environmentalism - Schlosberg, David (Oxford University Press, 1999)
In this theoretical treatment of the environmental justice movement, David Schlosberg demonstrates the development of a new form of critical pluralism. His study presents a challenge to both conventional pluralist thought and the practices of the major groups in the US environmental movement.
Keywords: Environmental justice -- United States.; Environmental policy -- United States.; Environmentalism -- Political aspects -- United States.; Cultural pluralism.; Cultural Diversity; Justice environnementale -- États-Unis.; Environnement -- Politique gouvernementale -- États-Unis.; Environnementalisme -- Aspect politique -- États-Unis.; Diversité culturelle.; BUSINESS & ECONOMICS -- Infrastructure.; SOCIAL SCIENCE -- General.; Cultural pluralism; Environmental justice; Environmental policy; Environmentalism -- Political aspects; United States